Roles for Mitochondrial Complex I Subunits in Regulating Synaptic Transmission and Growth - Mallik, Bhagaban; Frank, C. Andrew (Frontiers in Neuroscience, 2022)
To identify conserved components of synapse function that are also associated with human diseases, we conducted a genetic screen. We used the Drosophila melanogaster neuromuscular junction (NMJ) as a model. We employed RNA interference (RNAi) on selected targets and assayed synapse function and plasticity by electrophysiology. We focused our screen on genetic factors known to be conserved from human neurological or muscle functions (300 Drosophila lines screened). From our screen, knockdown of a Mitochondrial Complex I (MCI) subunit gene (ND-20L) lowered levels of NMJ neurotransmission. Due to the severity of the phenotype, we studied MCI function further. Knockdown of core MCI subunits concurrently in neurons and muscle led to impaired neurotransmission. We localized this neurotransmission function to the muscle. Pharmacology targeting MCI phenocopied the impaired neurotransmission phenotype. Finally, MCI subunit knockdowns or pharmacological inhibition led to profound cytological defects, including reduced NMJ growth and altered NMJ morphology. Mitochondria are essential for cellular bioenergetics and produce ATP through oxidative phosphorylation. Five multi-protein complexes achieve this task, and MCI is the largest. Impaired Mitochondrial Complex I subunits in humans are associated with disorders such as Parkinson’s disease, Leigh syndrome, and cardiomyopathy. Together, our data present an analysis of Complex I in the context of synapse function and plasticity. We speculate that in the context of human MCI dysfunction, similar neuronal and synaptic defects could contribute to pathogenesis.